Complications traumatiques et psychosociales des chutes chez le sujet âgé tunisien - Kechaou, Ines (Pan Afr Med J, 2019)
INTRODUCTION: Falls in the elderly are a major health problem due to their traumatic and psychosocial complications which may lead to a loss of autonomy and a state of dependency. This study aims to study the traumatic circumstances and psychosocial consequences of falls in the elderly. METHODS: We conducted a retrospective study of 40 patients aged 65 years and over with a history of at least one fall in the previous year between September 2014 and January 2016. They were enrolled among patients hospitalized or treated on an outpatient basis in the Department of Internal Medicine B in the Hospital Charles Nicolle. Data on circumstances and consequences of falls were collected through a retrospective interview with patients and their entourage about the fall. RESULTS: The average age of fallen patients was 75,7 years, with a female predominance (30F/10M). Precipitating factors were found in 38 patients. Extrinsic factors were found in 78.9% of cases while intrinsic factors in 50% of cases. Extended stay on the ground was reported in 10% of cases. Fractures were more frequent among women (12F/1M), especially involving upper limbs (61.5%). Psychosocial consequences were more frequent among women. Post-fall syndrome was found in 5 patients. CONCLUSION: The correction of the extrinsic and intrinsic precipitating factors of falls and the implementation of educational programs on how elderly should get up from the ground properly after a fall will prevent the risk of a fall as well as fall-related severe consequences.